PENERAPAN TEKNOLOGI WEB SERVICE UNTUK INTEGRASI LAYANAN E – TIKETING PEMESANAN TIKET TRAVEL DAN BIRO PERJALANAN PADA CV TRANS SUKSES (Information Technology and Telematics, 2015)
Abstract In the book travel tickets on a traveling company that society wants to book must come directly and conduct transactions directly in an order and the company can not directly inform the agent so the agent in the transaction between the agents of their agents are still manually.This can be overcome by creating a system that can be integrated by other systems in which to inform the traveling quickly and precisely and also real time .and can also serve booking tickets to the community in a practical and does not need to come directly to booking tickets or company transportrasiTo create a travel ticket booking application integration by leveraging web technology service.Sistem that can be integrated into other browsers / other systems and Enable a user to meakukan ticket reservations in real time and to make the application as a means of travel ticket booking in booking and traveling information.This study resulted in a web service application to provide integrated ticket booking services .. This application has a search feature Tickets Travel, Tour Packages search, search pemesanan..Penggunaan Status XML web service makes it easy to integrate the system to make this application as system integration ter. Developers who want to display the data in XML form only need to enter the parameters .The system will display the data in XML form corresponding parameters are entered and the results of the XML data can be processed by the developer as needed.Keywords: Web Service, XML, REST, GET, E ticketing Travel and Travel Agent